2015
DOI: 10.4066/amj.2015.2351
|View full text |Cite
|
Sign up to set email alerts
|

Long-term glycaemic control (HbA1c), not admission glucose, predicts hospital re-admission in diabetic patients

Abstract: Recognition and treatment of admission hyperglycaemia in diabetic patients was associated with longer LOS than if untreated. Contributory factors to LOS include: illness severity, infections, and higher HbA1c. Although follow-up plans were few (27 per cent) for diabetic patients with hyperglycaemia, it was significantly more likely in those with higher HbA1c. Diabetic patients' complexities require timely multidisciplinary team involvement. Improved follow-up care, particularly for hospitalised diabetic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…HbA1 C as an indicator of long-term glycemic control is a better predictor of hospital admission in patients with diabetes than the glucose levels on admission (Chai, Tonks, & Campbell, 2015). Many studies confirmed that various diets could improve glycemic control in people with type 2 diabetes (Banel & Hu, 2009; Gannon, Nuttall, Saeed, Jordan, & Hoover, 2003; Sauder, Mccrea, Ulbrecht, Krisetherton, & West, 2015; Q.…”
Section: Discussionmentioning
confidence: 99%
“…HbA1 C as an indicator of long-term glycemic control is a better predictor of hospital admission in patients with diabetes than the glucose levels on admission (Chai, Tonks, & Campbell, 2015). Many studies confirmed that various diets could improve glycemic control in people with type 2 diabetes (Banel & Hu, 2009; Gannon, Nuttall, Saeed, Jordan, & Hoover, 2003; Sauder, Mccrea, Ulbrecht, Krisetherton, & West, 2015; Q.…”
Section: Discussionmentioning
confidence: 99%
“…FPG was not considered in the present study for the diagnosis of diabetes because of the metabolic disturbances associated with AIS. Since HbA1c represents the long-term glycemic burden, it was considered as more reliable for the diagnosis of diabetes, [13] as per the Chinese guidelines. [14,15] Initial stroke severity was evaluated on the 1st day of admission according to the National Institute of Health Stroke Scale (NIHSS).…”
Section: Methodsmentioning
confidence: 99%
“…Hospitalisation typically results from short and/or long-term complications associated with poor blood sugar (i.e. glycaemic) control [ 5 ]. Thus, improving blood sugar control can significantly reduce the costs of diabetes-related care [ 1 ], reducing the economic burden of the disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indian, Pakistani, Bangladeshi) in particular are 2.6 times more likely to be admitted to hospital for diabetes, compared to Caucasians [ 8 ]. The excess hospitalisation risk in South Asian patients may denote higher complication rates resulting from poor blood sugar control [ 1 , 5 , 9 – 11 ]. Although some evidence suggests no ethnic differences in blood glucose levels [ 12 ], other research indicates poorer glycaemic control amongst South Asian patients relative to Caucasians [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation